2018
DOI: 10.1021/acs.jafc.8b00561
|View full text |Cite
|
Sign up to set email alerts
|

Oleocanthalic Acid, a Chemical Marker of Olive Oil Aging and Exposure to a High Storage Temperature with Potential Neuroprotective Activity

Abstract: The investigation of olive oils stored for a period of 24 months under appropriate conditions (25 °C, dark place, and airtight container) led to the identification of a new major phenolic ingredient, which was named oleocanthalic acid. The structure of the new compound was elucidated using one- and two-dimensional nuclear magnetic resonance in combination with tandem mass spectrometry. The new compound is an oxidation product of oleocanthal and is found in fresh oils in very low concentrations. The concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…On the other hand, oxygenated oleocanthal (oleocanthalic acid 48 ) and oxygenated ligstroside aglycone have the same molecular formula and precursor ion as oleacein and oleuropein aglycone, respectively, but their fragmentation originates different daughter ions 6 . Taxifolin, a phenolic compound of the flavonoid family with the same molecular weight as oleocanthal, can be found in olive oils at <1 mg Kg −1 49 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, oxygenated oleocanthal (oleocanthalic acid 48 ) and oxygenated ligstroside aglycone have the same molecular formula and precursor ion as oleacein and oleuropein aglycone, respectively, but their fragmentation originates different daughter ions 6 . Taxifolin, a phenolic compound of the flavonoid family with the same molecular weight as oleocanthal, can be found in olive oils at <1 mg Kg −1 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Oleacein and oleocanthal, with two aldehydic functional groups in an open configuration, possess larger reactivity than monoaldehyde oleuropein aglycone isomers, which are mainly present in a closed configuration [9]. Tsolakou et al [12] has proposed oleocanthalic acid formed by oxidation of oleocanthal as a marker of EVOO aging.…”
Section: Behavior Of Phenolic Compounds During Storagementioning
confidence: 99%
“…Oleacein and oleocanthal, with two aldehydic functional groups in an open configuration, possess larger reactivity than monoaldehyde oleuropein aglycone isomers, which are mainly present in a closed configuration [10]. Tsolakou et al [12] has proposed oleocanthalic acid formed by oxidation of oleocanthal as a marker of EVOO ageing.…”
Section: Behavior Of Phenolic Compounds During Storagementioning
confidence: 99%
“…Several studies have demonstrated the effects of storage conditions on oil phenols, reporting a decrease in total phenolic content, oxidation of secoiridoid derivatives and increases in hydroxytyrosol and tyrosol, among others [1,[10][11][12][13]. Although a specific phenolic content or composition is not included in the IOC Trade Standard [2], a decrease in its content or significant changes in its composition can affect the stability of olive oils [6,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation